Parrot in the oven : mi vida : a novel - Martinez, Victor, 1954-2011. (New York : Harper Trophy, 2005)
Manny relates his coming of age experiences as a member of a poor Mexican American family in which the alcoholic father only adds to everyone's struggle.
'Joanna Cotler books.'
Includes reader's guide.
National Book Award winner. Winner of the Pura Belpre Award.
Keywords: Families -- Fiction; Alcoholism -- Fiction; Mexican Americans -- Fiction; National Book Awards